Narečno besedje iz pomenskega polja sadovnjak v Murkovem drsteljskem govoru - Koletnik, Mihaela (Slavia Centralis, 2020)
DIALECT WORDS FROM THE SEMANTIC FIELD OF ORCHARD IN MURKO’S DRSTELJA SUBDIALECT The present article addresses the dialect words from the semantic field of orchard. The Drstelja subdialect, the subdialect of Murko’s birthplace, is categorised by the Slovenian dialectologist as a Prlekija dialect of the Pannonian dialect group. The chosen vocabulary, which can be classified into several smaller thematic groups, is presented in the form of dictionary entries arranged in alphabetical order and presented in view of its structural, etymological and word formation characteristics.